AÇIK KAYNAK KODLU VE TİCARİ WEB TABANLI UZAKTAN EĞİTİM YAZILIMLARININ KARŞILAŞTIRILMASI. - AYDOĞDU KARAASLAN, İlknur (Journal of International Social Research / Uluslararası Sosyal Araştırmalar Dergisi, 2019)
Different software programs have been developed in the field of education. This software is designed to create the framework of distance education. The lack of space in educational institutions, overpopulation, the increase in the need to receive education without continuing education in society are some of the reasons in front of the distance education. Not only educational institutions, but also companies prefer distance education to prioritize economy in personnel education and to prevent loss of time. The number of students enrolled for online education is increasing. In particular, time and space Independent Education is preferred for Master and doctorate education. Therefore, the use of existing software tools and technology in education and training is gaining importance. Today, there are many educational software. Each educational institution prefers educational software that can be adapted to their academic standards, curricula and assessment tools. In this study, education software, which are used in Turkey and in the world today are classified as commercial and open source, examined in detail in terms of its characteristics.